LOAN PORTFOLIO COMPOSITION OF ISLAMIC AND CONVENTIONAL BANKS PRE- AND POST-COVID-19 PANDEMIC? CASE OF INDONESIA - Dawood Ashraf; Muhammad Suhail Rizwan; Danny Hermawan Adiwibowo; Richard Irfan Yusan (Bank Indonesia, 2022)
This study investigates how the Covid-19 pandemic has affected the loan portfolio composition of Indonesian Islamic and conventional banks. By using a sample of 108 conventional and 9 Islamic banks, we find that conventional banks issued more consumption loans during the sample period. On the contrary, Islamic banks granted more investment loans than consumption loans. In addition, given limited support from the central bank, Islamic banks still increased their contribution to investment loans portfolio more rapidly during the COVID-19 pandemic. These results support the view that Islamic banks provide funding to long-term investment projects and may contribute more to sustainable economic growth. This finding could have policy implications for both Islamic banks and the government. Despite the fact that Islamic banking is in its infancy in Indonesia, it provides funding for the real economy. Regulators may assist the Islamic banking sector in developing risk management capacity in various sectors, including agriculture, manufacturing, trading, distribution, hotels, and restaurants. Furthermore, implementing a well-integrated policy framework that includes monetary, fiscal, and financial services can also assist in optimizing the momentum of economic recovery after the pandemic despite global supply disruptions, the Russian-Ukraine war, and climate change.